Terjemah Sirr al-Asrar / Syekh Abdul Qadir Al-Jailani ; penerjemah, Abdul Majid Hj. Khatib ; editor, Sabrur - ABDUL QADIR AL-JAILANI , Syekh , 470 H (1077-1078 M); Abdul Majid Hj. Khatib; Sabrur (Diva Press, 2017)
380 hlm. ; 24 cm.